Conhecimentos e atitudes de trabalhadores rurais sobre o uso de agrotóxicos - Figueiredo, Fabiana Coutinho Pimenta (2015)
The exposure of workers to pesticides occurs especially in the agricultural sector and rural areas and in general can lead to health problems such as intoxication or cronic illness. The aim of this study was to identify the knowledge and the attitudes of rural workers about risks health of handle pesticides. It is a descriptive exploratory research performed in the region of Patos de Minas, Minas Gerais, Brazil. A semi-structured instrument was used to interview thirteen rural workers, from June 2013 to May 2014. Data were risen on the knowledge of participants about the risks of handle pesticides the usage of individual protective equipment, exposure to hazards, signs and symptoms of pesticide toxicity. The interviews were recorded, transcribed and analyzed following the method of content analysis. All the participants were male, age between 21-55 years old and studied six years, in average. They have been handle pesticides in cultures of coffee, corn, soy, beans, cane sugar, tomatoes and fruits. Most of the participants referred knowledge and information about the risks of handle pesticides and to have information about handle pesticides, with one exception. They also referred use of individual protective equipments, however in incomplete or inadequate way. Some participants reported symptoms of poisoning and diseases caused by pesticides, although they awere about the relationship between handle pesticides and pesticide toxicity symptoms. The results suggest that there is divergence among knowledge referred and attitudes concerning pesticides. For participants, fully protective equipments caused a lot of heat, but accepted the inadequate working conditions as a necessity. The main factors that can lead to this situation are poor working conditions, individual protective equipments unsuitable to the climate of the region, lack of information and misunderstanding of technical language, aggravated by low education background. This is a scenario of human and environmental exposure to pesticides and social vulnerability, which requires the implementation of educational actions and labor inspection mesures.